2015
DOI: 10.1111/head.12585
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement‐Based Economics – What Is It and How Can We Use It to Inform Drug Policy Reform?

Abstract: Background.-In Ontario, approximately $3.8 billion is spent annually on publicly funded drug programs. The annual growth in Ontario Public Drug Program (OPDP) expenditure has been limited to 1.2% over the course of 3 years. Concurrently, the Ontario Drug Policy Research Network (ODPRN) was appointed to conduct drug class review research relating to formulary modernization within the OPDP. Drug class reviews by ODPRN incorporate a novel methodological technique called reimbursement-based economics, which focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It can be challenging to decide on a reasonable price for a new drug if the agent is highly innovative and meets an unfulfilled need, but the company is asking a very high price. Various new approaches to evaluate a drug for funding have been proposed [ 28 ], but there is no perfect method to determine what should and should not be funded.…”
Section: Drug Fundingmentioning
confidence: 99%
“…It can be challenging to decide on a reasonable price for a new drug if the agent is highly innovative and meets an unfulfilled need, but the company is asking a very high price. Various new approaches to evaluate a drug for funding have been proposed [ 28 ], but there is no perfect method to determine what should and should not be funded.…”
Section: Drug Fundingmentioning
confidence: 99%
“…The last component of the review is the economic evaluation, which applies a pragmatic approach to pharmacoeconomic research focusing on assessing the economic impact of different drug reimbursement models (9). Analyses are conducted by identifying appropriate modeling frameworks for each drug-class, with a strong focus on identifying the optimal reimbursement model considering both budget impact and cost-effectiveness.…”
Section: Research Componentsmentioning
confidence: 99%
“…A systematic review of the cost‐effectiveness literature identified a total of 21 published economic analyses of triptan use. Overall, the weight of evidence suggests that triptans are cost‐effective relative to other acute migraine treatments, including ergots and aspirin (acetylsalicylic acid) in combination with an antiemetic …”
Section: Step 5: Reimbursement Based Economicsmentioning
confidence: 99%
“…Several alternative reimbursement strategies were considered in the reimbursement‐based economic analysis including maintaining triptans on EAP or changing the listing to general benefit or Limited Use (Table ) . Limited Use is a much less restrictive option for reimbursement than EAP, and results in increased accessibility to applicable individuals under the ODB program.…”
Section: Step 5: Reimbursement Based Economicsmentioning
confidence: 99%